Teachers' Professional Code of Conduct and its Application on Teaching Professionalism: A Case Study of Kigoma Ujiji,Tanzania - Shaibu K. Shaibu; Prospery M. Mwila (PT. Pusmedia Group Indonesia, 2025)
This study addresses the gap between teachers’ awareness of professional codes of conduct and their actual application in the Kigoma Ujiji municipality, Tanzania, and examines the negative impact this has on teaching professionalism. Despite the existence of ethical guidelines, many teachers fail to adhere to them, leading to challenges such as sexual violence, low academic performance, and a disrupted educational environment. These issues not only compromise the quality of education but also affect the well-being of students. The study explores the role of teachers' professional codes of conduct in enhancing teaching professionalism in Kigoma Ujiji. A qualitative research approach with a descriptive analysis design was employed, involving the target population of 15 teachers from 5 schools, along with 1 District Education Officer (DEO), 5 Ward Education Officers (WEO), and 1 representative from the Teacher Services Commission (TSC). A combination of probability and non-probability sampling techniques was used, with simple random sampling for teachers and non-probability sampling for education officers. Data was collected through semi-structured interviews and questionnaires. The results show that while many teachers are aware of professional codes of conduct, there is a significant gap in their application, leading to unethical behavior such as inappropriate relationships with students. This has contributed to school dropouts, low academic performance, early pregnancies, and community conflicts. The study emphasizes the need for better enforcement of ethical standards, more comprehensive teacher training, and the implementation of stricter policies to protect students from exploitation. Recommendations include strengthening monitoring mechanisms and providing ongoing professional development to ensure teachers align their practices with established ethical guidelines, improving the overall educational environment